Feminism, Citizenship, and Reception of the 1973 Chilean Coup in the Alianza de Mujeres Costarricenses (AMC) - Moreno Vargas, María Daniela (2024)
This article examines a reflection on the concept of female citizenship and materialist feminism in the first section. Subsequently, this article is also divided into two sections: the political participation of women in the second half of the twentieth century in Latin America and the study of the reception of the coup in Chile by the Alianza de Mujeres Costarricenses (AMC) from the theoretical approach of maternal feminism. The aim of this study is to analyze the reception of the political event by AMC that shook the Latin American people in general in 1973 within the context of the Cold War and the second wave of feminism in Latin America, being key for the development of women's social movements. To achieve this, we analyzed the discourse presented in publications made by the women's newspaper Nuestra Voz about this coup.